Sub-Doppler laser cooling of 40K with Raman gray molasses on the D2 line. (12th April 2017) - Bruce, G D; Haller, E; Peaudecerf, B; Cotta, D A; Andia, M; Wu, S; Johnson, M Y H; Lovett, B W; Kuhr, S
Abstract: Gray molasses is a powerful tool for sub-Doppler laser cooling of atoms to low temperatures. For alkaline atoms, this technique is commonly implemented with cooling lasers which are blue-detuned from either the D 1 or D 2 line. Here we show that efficient gray molasses can be implemented on the D 2 line of 40 K with red -detuned lasers. We obtained temperatures of 48 ( 2 ) μ K, which enables direct loading of 9.2 ( 3 ) × 10 6 atoms from a magneto-optical trap into an optical dipole trap. We support our findings by a one-dimensional model and three-dimensional numerical simulations of the optical Bloch equations which qualitatively reproduce the experimentally observed cooling effects.